Bone Marrow Morphology and Immunophenotypic Expression in De-Novo Acute Leukaemia (Bangladesh Medical Journal, 2025)
Acute leukaemias are a heterogeneous group of hematologic malignancies with diverse morphologic and immunophenotypic profiles. It’s characteristics differ in clinical, morphological, immunophenotypic, genetic, and molecular perspective. Despite the increasing importance of molecular and genetic features in the classification of acute leukemias, morphological and immunophenotypic analysis remains the primary method to diagnose acute leukemia for initial evaluation and to guide specific molecular genetic tests.  This study was conducted to observe the immunophenotypic patterns and their morphological expression among patients with acute leukemia, and to find the correlation between the immunophenotypic markers and the different French-American-British (FAB) sub-classifications of acute leukemias. This descriptive cross-sectional study was designed to evaluate the extent and correlation of bone marrow morphological features with immunophenotypic expression in patients with de-novo acute leukaemia (AL) and to determine discrepancies between morphology and immunophenotyping. This study was conducted in the Department of Haematology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from January 2017 to June 2018. Fifty (50) newly diagnosed de-novo AL patients were evaluated through bone marrow morphology and flow cytometric immunophenotyping. The Beckman Coulter Cytomics FC 500 was used to analyze surface and cytoplasmic antigens. Data were analyzed using SPSS v23 with descriptive and inferential statistics. Among 50 patients, 30 (60%) were male and 20 (40%) female. The predominant age group was 19 to 29 years (42%). Morphologically, two-third (66%) cases were acute myeloid leukaemia (AML) and one-third (34%) acute lymphoblastic leukaemia (ALL). Among AML cases, the most frequent FAB subtypes were M1 (24%), M2 (20%), and M4 (14%); among ALL cases, L2 subtype was most common (20%). Immunophenotyping identified one-third (66%) of  AML, 28% B-ALL, 6% T-ALL, and 4% mixed phenotypic acute leukaemia (MPAL). Expression positivity was highest for CD45 (94%), cMPO (66%), and HLA-DR (78%). Discrepancy between morphology and immunophenotype was observed in 12% cases. Bone marrow morphology remains essential in the initial evaluation of de-novo acute leukaemia, but immunophenotyping provides critical complementary data for accurate subtyping. A 12% diagnostic discrepancy highlights the necessity for integrated morphologic-immunophenotypic assessment to ensure precise classification and guide targeted therapy.Bangladesh Med J. 2024 Sept; 53(3): 31-35